Permissive Hypercapnia Results in Decreased Functional Vessel Density in the Skin of Extremely Low Birth Weight Infants - Puchwein-Schwepcke, Alexandra Francoise; Schottmayer, Kristina; Mormanová, Zuzana; Dreyhaupt, Jens; Genzel-Boroviczeny, Orsolya; Thome, Ulrich H. (Frontiers in Pediatrics, 2018)
Background: Ventilator induced lung injury with subsequent bronchopulmonary dysplasia remains an important issue in the care of extremely low birthweight infants (ELBW). Permissive hypercapnia has been proposed to reduce lung injury. Hypercapnia changes cerebral perfusion but its influence on the peripheral microcirculation is unknown. Methods: Data were collected from 12 infants, who were randomized to a permissive High PCO2 Target group (HTG) or a Control group (CG). Inclusion criteria were birth weight between 400g and 1000g, gestational age from 23 to 28 6/7 weeks, intubation during the first 24 hours of life and no malformations. The PCO2 target range was increased stepwise in both groups for weaning and was always 15mmHg higher in the HTG than in the CG. Skin microvascular parameters were assessed non-invasively with Sidestream Dark Field imaging on the inner side of the right arm every 24 hours during the first week of life and on the 14th day of life. Results: Infants in the HTG had significantly higher max. PCO2 exposure, which was associated with a significantly and progressively reduced functional vessel density (FVD, P<0.01). Moreover, there were significant differences in the diameter distribution over time, with HTG subjects having fewer small vessels but more large vessels. Conclusions: High PCO2 levels significantly impaired peripheral microcirculation in preterm infants, as shown by a decreased FVD, presumably secondary to peripheral vasoconstriction. (ISRCTN 56143743)